Predator-prey-subsidy population dynamics on stepping-stone domains with dispersal delays. (14th August 2018) - Eide, Ragna M.; Krause, Andrew L.; Fadai, Nabil T.; Van Gorder, Robert A.
Highlights: Impact of access to food resources on the stability and behaviour of the predator-prey-subsidy system is investigated. We focus on how incorporating travel time changes the temporal dynamics. Travel time is incorporated as discrete delay in the network diffusion term in order to model time taken to migrate between spatial regions. Temporal delay alone does not push species into extinction, but rather may stabilize or destabilize coexistence equilibria. Incorporation of dispersal delay has a regularizing effect on dynamics, suggesting that dispersal delay can be proposed as a solution to the paradox of enrichment. Abstract: We examine the role of the travel time of a predator along a spatial network on predator-prey population interactions, where the predator is able to partially or fully sustain itself on a resource subsidy. The impact of access to food resources on the stability and behaviour of the predator-prey-subsidy system is investigated, with a primary focus on how incorporating travel time changes the dynamics. The population interactions are modelled by a system of delay differential equations, where travel time is incorporated as discrete delay in the network diffusion term in order to model time taken to migrate between spatial regions. The model is motivated by the Arctic ecosystem, where the Arctic fox consumes both hunted lemming and scavenged seal carcass. The fox travels out on sea ice, in addition to quadrennially migrating over substantial distances. We model the spatial predator-prey-subsidy dynamics through a "stepping-stone" approach. We find that a temporal delay alone does not push species into extinction, but rather may stabilize or destabilize coexistence equilibria. We are able to show that delay can stabilize quasi-periodic or chaotic dynamics, and conclude that the incorporation of dispersal delay has a regularizing effect on dynamics, suggesting that dispersal delay can be proposed as a solution to the paradox of enrichment.